Antheraea pernyi Silk Fiber: A Potential Resource for Artificially Biospinning Spider Dragline Silk - Zhang, Yaopeng (Hindawi Publishing Corporation, 2010)
The outstanding properties of spider dragline silk are likely to be determined by a combination of the primary sequences and the secondary structure of the silk proteins. Antheraea pernyi silk has more similar sequences to spider dragline silk than the silk from its domestic counterpart, Bombyx mori. This makes it much potential as a resource for biospinning spider dragline silk. This paper further verified its possibility as the resource from the mechanical properties and the structures of the A. pernyi silks prepared by forcible reeling. It is surprising that the stress-strain curves of the A. pernyi fibers show similar sigmoidal shape to those of spider dragline silk. Under a controlled reeling speed of 95 mm/s, the breaking energy was 1.04 × 10(5) J/kg, the tensile strength was 639 MPa and the initial modulus was 9.9 GPa. It should be noted that this breaking energy of the A. pernyi silk approaches that of spider dragline silk. The tensile properties, the optical orientation and the β-sheet structure contents of the silk fibers are remarkably increased by raising the spinning speeds up to 95 mm/s.